Improvement Of Internal Quality Assurance System Based On ISO 9001:2008 With Document Management Control (DMC) And Web Based Application - Hermien tridayanti; Bayu Airlangga Putra; Ani Wulandari (LPPM of NAROTAMA UNIVERSITY, 2018)
Managing the enactment of an internal quality assurance system requires the proper implementation of internal quality assurance to ensure the quality of Higher Education. The global challenges and dynamics of the development of information technology make Indonesian universities somewhat under pressure. higher education institutions are required to be able to handle changes, both internally and externally, to further strengthen the quality of the learning process. For this reason internal quality assurance plays an intense role in education services. The quality policy of the internal quality assurance system describes an explanation of how a university understands, designs and implements their internal quality assurance system in the provision of higher education services to build, manage and maintain a quality culture. In these documents there is an explanation of backgrounds, objectives, and strategies, to improve the quality in every done task. In the global era, the nature of day-to-day operations tends to get more sophisticated and complex, therefore the internal quality assurance system must be supported by an integrated system in internal processes using information technology such as Document Management Control. Create quality holistic cycles that work best with the uniqueness of the institution itself. This will then result in a